The climatic mass balance of Svalbard glaciers: a 10-year simulation with a coupled atmosphere-glacier mass balance model - Aas, Kjetil; Dunse, Thorben; Collier, Sarah; Schuler, Thomas; Berntsen, Terje; Kohler, Jack; Luks, Bartłomiej (Cryosphere, 2016)
In this study we simulate the climatic mass balance of Svalbard glaciers with a coupled atmosphere-glacier model with 3 km grid spacing, from September 2003 to September 2013. We find a mean specific net mass balance of -257 mm w.e.aEuro-yr(-1), corresponding to a mean annual mass loss of about 8.7 Gt, with large interannual variability. Our results are compared with a comprehensive set of mass balance, meteorological, and satellite measurements. Model temperature biases of 0.19 and -1.9aEuro-A degrees C are found at two glacier automatic weather station sites. Simulated climatic mass balance is mostly within about 100 mm w.e.aEuro-yr(-1) of stake measurements, and simulated winter accumulation at the Austfonna ice cap shows mean absolute errors of 47 and 67 mm w.e.aEuro-yr(-1) when compared to radar-derived values for the selected years 2004 and 2006. Comparison of modeled surface height changes from 2003 to 2008, and satellite altimetry reveals good agreement in both mean values and regional differences. The largest deviations from observations are found for winter accumulation at Hansbreen (up to around 1000 mm w.e.aEuro-yr(-1)), a site where sub-grid topography and wind redistribution of snow are important factors. Comparison with simulations using 9 km grid spacing reveal considerable differences on regional and local scales. In addition, 3 km grid spacing allows for a much more detailed comparison with observations than what is possible with 9 km grid spacing. Further decreasing the grid spacing to 1 km appears to be less significant, although in general precipitation amounts increase with resolution. Altogether, the model compares well with observations and offers possibilities for studying glacier climatic mass balance on Svalbard both historically as well as based on climate projections.